Investigating the effects of graphene nanoplatelets on the mechanical properties of Engineered Cementitious Composite - Yenn, Loo Chi (Universiti Teknologi PETRONAS, 2020)
With the advancement of nanotechnology, nanomaterial has been considered to have the potential in enhancing the strength of cementitious composites. The incorporation of graphene nanoplatelets (GNPs) as a nano-filler has achieved excellent results in terms of the performance of structures. As can be observed from the surroundings, high-performance structures like bridges are in seriously damaged conditions due to severe environmental conditions, poor maintenance, and heavy vehicle load. Although ECC has been utilized for repairing and retrofitting of bridges, that is by applying one layer of ECC on the based concrete, the long-term durability of structure is still not achieved yet. In order to further increase the service life of bridges, durable material is required to achieve the long-term durability of structure. As mentioned above, GNPs is a potential candidate for enhancing the strength of structures. Therefore, the effects of GNPs on the mechanical properties of engineered cementitious composites were investigated.